Economic Analyses of The Cultural and Creative Industries in Slovenia - Nika Murovec; Damjan Kavaš (Naše gospodarstvo/Our economy, 2012)
This paper presents results of the qualitative and quantitative economic analyses of the cultural and creative industries (CCI), which were carried out within two projects: “Creati- ve Cities” and “The state of design, with a focus on industrial design, as a part of creative industries, and best international practices as a foundation for fostering this sector in Slovenia.” This paper tacked the several methodological issues related to CCI analysis by combining different methodological approaches in order to improve their reliability. The main results of the public sector, industrial, occupational, and SWOT (strengths, weaknesses, opportunities, threats) analyses are described. CCI in Slovenia presented as a potential that has not been fully mobilised. In order to further develop CCI and exploit the economic potential, a comprehensive policy support of CCI at the local, national, and EU levels is needed.